Pembentukan Karakter Melalui Profil Pelajar Pancasila - Nur Aini; Nikmatul Hasanah; Nadya Prandika; Nadia Fitri Jeni; Mutyas Sandi Prabowo (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to determine the profile of Pancasila students as an effort to realize national character. The method used in this study uses a library research method or approach, with library data collection methods. The results of this research show that the Pancasila student profile is one of the policies that supports the realization of national education goals and the continuation of the character strengthening program. Through the application of the 6 dimensions of the Pancasila student profile, it is hoped that the Indonesian nation will become individuals who are intelligent and have character and are able to face the challenges of the 21st century and of course instill the values contained in Pancasila as our country's philosophy consistently and ultimately be able to realize a prosperous and dignified national life. Strategy The development of the Pancasila student profile is carried out through integration in formal education activities through intracurricular, co-curricular and extracurricular activities which are packaged in project activities to strengthen the Pancasila student profile through the implementation of the Pancasila student profile policy. It is hoped that this will be able to build a superior Indonesian national character and be able to compete globally.